Near-term embryos and gravid females of Lusitanian cownose ray (Rhinoptera marginata) in Mersin Bay, eastern Mediterranean Sea - Tirasin, E. Mumtaz; Basusta, Nuri (Csiro Publishing, 2018)
Batoid chondrichthyans are vulnerable to commercial fisheries even though they are often not targeted. A greater understanding of their reproductive biology is important to facilitate their conservation. In February 2013, 89 female and 40 male Lusitanian cownose ray (Rhinoptera marginata) specimens were accidentally caught in Mersin Bay in the eastern Mediterranean Sea. Thirty-six fish were gravid, each bearing one embryo. Of the remaining females, 39 were sexually mature but not gravid and 14 were immature. There were 28 mature and 12 immature males. The average disc width (DW) of both mature females (80.2cm) and males (74.2cm) was significantly higher than that of immature females (60.7cm) and males (60.3cm). For all rays, DW and total weight (TW) were in the range 55.7-98.2cm and 1802-13600g. The DW and TW measured for all 16 female and 20 male embryos were in the range 15.6-29.2cm and 57-281g. Such a large single haul sample, including many gravid specimens and mature males, indicates a schooling formation at capture. The location in Mersin Bay near the estuaries of the Tarsus and Seyhan rivers, and its relative closeness to the sampling location of a previously reported neonate, suggests that this region may be a nursery area for Lusitanian cownose rays in the eastern Mediterranean.
Keywords: nursery ground; reproduction biology; weight-length relationship